New insights into RF and microwave drying of foods - Renshaw, Ryan C. (2017)
This work reports a fundamental study of the science and economics of microwave and RF drying of foods, addressing current knowledge gaps and introducing new techniques to aid the development of new microwave and RF drying processes.